Study of the interaction between HSV-1 and a native-like supported lipid bilayer with total internal reflection fluorescence microscopy - Schmidt, Eneas (My University, 2016)
Viruses pose a great threat to human health because many viral diseases have no cure to this day and new viruses are likely to emerge in the future. There is therefore a continuous need for the development of vaccines and anti-viral pharmaceuticals. Moreover, platforms making it possible to measure the effectiveness of potential antiviral drugs are urgently needed to accelerate the development progress of antiviral drugs. The available screening systems today are often either cell-based systems or basic interaction platforms. Accordingly they are either expensive or very simplified. A new approach to antiviral drug screening, in particular in the context of virus binding inhibitors, that is cheaper and easier to maintain compared to cell-based systems but still preserves some of the complexity of a native system, is an in vitro platform based on native-like supported lipid bilayers (SLBs). Such a system focuses on the interaction of the virus with the cell membrane, and the inhibition of this interaction to prevent infection. In this project, an in vitro screening platform for use with the herpes simplex virus (HSV) was developed, based on the extraction of native membrane material from green monkey kidney (GMK) cells. Association and dissociation events between fluorescently labeled herpes simplex virus type 1 (HSV-1) and native membrane SLBs were examined with total internal fluorescence (TIRF) microscopy. The binding kinetics could be extracted with equilibrium fluctuation analysis, a method based on the observation of the binding and release process of individual virus particles. As a first application of this platform, a mutant strain of HSV-1 lacking the membrane bound glycoprotein C (gC), a ligand that facilitates the attachment to native membranes was compared to the wildtype HSV-1 KOS strain. As expected, the results showed that that the gC deficient strain had significantly less binding compared to the wildtype. Additionally an inhibition study was performed with the glycosaminoglycan (GAG) heparin to determine its effect on binding. The heparin inhibition study revealed a dose dependent inhibitory response. The results demonstrate the functionality of the platform and its ability to measure specific binding interactions. This shows the potential of the sensor platform to be used as a bioanalytical screening tool for antiviral drug testing.
Keywords: Fysik; Physical Sciences